The investigation of attention properties in normal and abnormal children - Lygis , D. (Psichologija, 1981)
Concentration, distribution and switching of acoustic, visual and tactile attention in blind, light-sighted, deaf, mentally retarded and normal children (on the average 19 years of age) were studied. It has been found that audio-tactual and audio-visual distribution of attention combine well (the average decrement of performance constitutes 14.5%) in comparison with visual-tactual distribution (the average decrement of performance constitutes 40.2%). According to the index of velocity of attention concentration, the subject groups distributed themselves as follows: blind, normal, light-sighted, deaf and mentally retarded. According to the index of attention switching, the subject groups distributed themselves in the following order: light-sighted, normal, mentally retarded and deaf. According to the index of intermodal distribution of attention, the subject groups distributed themselves in the following way: blind, normal, light-sighted, mentally retarded and deaf.
Keywords: attention; deafness; blindness; attention distribution; attention switching